Statistics: using regression models. (9th May 2013) - Scott, M.; Flaherty, D.; Currall, J.
Abstract : In a previous article, we asked the simple question "Are we related?" and used scatterplots and correlation coefficients to provide an answer. In this article, we will take this question and reword it to "How are we related?" and will demonstrate the statistical techniques required to reach a conclusion.